2013
DOI: 10.2174/1566523211313020004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Human Disease with Pluripotent Stem Cells

Abstract: Recent progress in the field of cellular reprogramming has opened up the doors to a new era of disease modelling, as pluripotent stem cells representing a myriad of genetic diseases can now be produced from patient tissue. These cells can be expanded and differentiated to produce a potentially limitless supply of the affected cell type, which can then be used as a tool to improve understanding of disease mechanisms and test therapeutic interventions. This process requires high levels of scrutiny and validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…Derived from adult cell types, iPSC have enabled the creation of patient-specific stem cells, giving the opportunity to identify aberrant disease-associated pathways allowing disease modeling [454][455][456]. iPSC are used for in vitro development and testing of new therapeutic agents and regimens [457], for high-throughput drug screening [458,459] and imaging in industrial platforms [460].…”
Section: Induced Pluripotent Stem Cells (Ipsc)mentioning
confidence: 99%
“…Derived from adult cell types, iPSC have enabled the creation of patient-specific stem cells, giving the opportunity to identify aberrant disease-associated pathways allowing disease modeling [454][455][456]. iPSC are used for in vitro development and testing of new therapeutic agents and regimens [457], for high-throughput drug screening [458,459] and imaging in industrial platforms [460].…”
Section: Induced Pluripotent Stem Cells (Ipsc)mentioning
confidence: 99%
“…201312). Additionally, hiPSCs, derived from patients can be utilised to interrogate disease mechanisms and provide a potential source of autologous cells for regenerative medicine13.…”
mentioning
confidence: 99%
“…Global DNA promoter methylation and gene expression analyses comparing cancer cell lines to their reprogrammed counterparts showed that reprogramming resulted in significant epigenetic remodeling of oncogenes and tumor suppressors [78]. As discussed above and reviewed in other articles [57,63,79], it is speculated that the therapuetic potential of cancer cell reprogramming is mainly driven by epigenetic remodeling which reversed the observed dysfunction. Therefore it can be suggested that cellular reprogramming may be used as a potential epigenetic therapy for cancer.…”
Section: Cancer Cell Reprogramming As Therapymentioning
confidence: 94%
“…As detailed above, cellular reprogramming and tumorigenesis share a lot of features including epigenetic mechanisms therefore reprogramming of cancer cells may result in epigenetic remodeling which can reverse the observed dysfunction. As discussed in previous sections, most of the studies that showed reduced tumorigenicity of differentiated cancer iPS cells found that extensive epigenetic remodeling of tumor suppressor genes and oncogenes can arise during cellular reprogramming [78,79]. In a study by Zhang et al, DNA promoter methylation analyses indicated that epigenetic remodeling of oncogene promoters (such as myc) results in a chromatin permissive state in which silencing by another signal is possible.…”
Section: Important Factors For Cancer Cell Reprogrammingmentioning
confidence: 95%